Case Notes: Factors Influencing the Adoption of Virtual Desktop Infrastructure (VDI) Within the South African Banking Sector - Sekwakwa, Matthews; Mokwena, Sello (My University, 2015)
In the 21st century, portable computers and wide area networks are fast becoming the paradigm for computing presence in commercial and industrial settings. The concept of virtualisation in computing originated in the 1960s. Several virtualisation technologies have emerged over the past decade, with the most notable being VMWare, Citrix and Microsoft VDI solutions, including Azure RemoteApp. This paper explores factors influencing the adoption of VDI in the South African banking sector by implementing Rogers’ “perceived characteristics of innovations”. The study found that the relative advantage of VDI, as perceived in banking institutions, includes improved data security and staff working experience; reduced time to deploy devices; and reduced computer downtime. The findings on compatibility factors indicate that good VDI compatibility with legacy software and hardware has a direct relationship with users’ successful adoption. The findings on complexity of use show that other factors, such as the flexibility that comes with remote access, may be a greater influence on adoption than ease of use. Observability of reduced IT support time and increased productivity of remote access have a positive relationship with adoption.
Keywords: virtual desktop infrastructure, VDI, virtualisation, thin client, innovation in banking, perceived characteristics of innovations